2012
DOI: 10.1071/is12038
|View full text |Cite
|
Sign up to set email alerts
|

What happens to the traditional taxonomy when a well-known tropical saturniid moth fauna is DNA barcoded?

Abstract: Biodiversity of tropical Saturniidae, as measured through traditionally described and catalogued species, strongly risks pooling cryptic species under one name. We examined the DNA barcodes, morphology, habitus and ecology of 32 ‘well known’ species of dry forest saturniid moths from Area de Conservacion Guanacaste (ACG) in north-western Costa Rica and found that they contain as many as 49 biological entities that are probably separate species. The most prominent splitting of traditional species – Eacles imper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Diet-mixing is also predicted under the physiological-efficiency hypothesis to reduce the build up of defensive chemicals and counteract nutritional deficiencies that may arise from single-host diets (Held & Potter, 2004;Franzke et al, 2010;Karban et al, 2010). However, DNA barcoding has shown that some widespread, generalist species are actually complexes of multiple closely related host-specific species (Hebert et al, 2004;Janzen et al, 2009Janzen et al, , 2012Valentini, Pompanon & Taberlet, 2009; but see Hulcr et al, 2007a). It therefore may be that generalists are rarer than is currently appreciated.…”
Section: Host Specialisationmentioning
confidence: 89%
“…Diet-mixing is also predicted under the physiological-efficiency hypothesis to reduce the build up of defensive chemicals and counteract nutritional deficiencies that may arise from single-host diets (Held & Potter, 2004;Franzke et al, 2010;Karban et al, 2010). However, DNA barcoding has shown that some widespread, generalist species are actually complexes of multiple closely related host-specific species (Hebert et al, 2004;Janzen et al, 2009Janzen et al, , 2012Valentini, Pompanon & Taberlet, 2009; but see Hulcr et al, 2007a). It therefore may be that generalists are rarer than is currently appreciated.…”
Section: Host Specialisationmentioning
confidence: 89%
“…Saturniid caterpillars tend to be relatively polyphagous and to prefer old, tough, tannin‐rich leaves (Bernays & Janzen, ). In contrast to other moth families such as Crambidae, Erebidae, or Geometridae, local species pools of Saturniidae are rather restricted, usually with <100 species in the Neotropics (Janzen et al., ; Lamarre et al., ; Lamas, ). The relatively low local species richness of Saturniidae facilitates the compilation of exhaustive lists for comparative ecological studies and long‐term monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…This has provided an additional layer of data to study the ACG species of caterpillars, parasitoids, and food plants (e.g., Smith et al 2006, 2007, 2008; Whitfield et al 2012; Janzen et al 2011, 2012). …”
Section: Introductionmentioning
confidence: 99%